2011
DOI: 10.1186/1472-6963-11-282
|View full text |Cite
|
Sign up to set email alerts
|

Inputs to quality: supervision, management, and community involvement in health facilities in Egypt in 2004

Abstract: BackgroundAs low- and middle-income countries experience economic development, ensuring quality of health care delivery is a central component of health reform. Nevertheless, health reforms in low- and middle-income countries have focused more on access to services rather than the quality of these services, and reporting on quality has been limited. In the present study, we sought to examine the prevalence and regional variation in key management practices in Egyptian health facilities within three domains: su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Only four studies located in the medical literature databases reported using a standardized assessment tool thereby meeting the inclusion criteria. Of these, three reported using the Service Provision Assessment ( Hong et al 2006 ; Agha and Do 2009 ; Cherlin et al 2011 ) and one reported using the Health Facility Census ( Gabrysch et al 2011 ); both of these tools were also located in the IHFAN database. None of the four studies included copies of the tools ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies located in the medical literature databases reported using a standardized assessment tool thereby meeting the inclusion criteria. Of these, three reported using the Service Provision Assessment ( Hong et al 2006 ; Agha and Do 2009 ; Cherlin et al 2011 ) and one reported using the Health Facility Census ( Gabrysch et al 2011 ); both of these tools were also located in the IHFAN database. None of the four studies included copies of the tools ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some health facilities have already received international accreditation certificates, but the vast majority of the health facilities still require targeted efforts to improve the quality of care. 21 –25…”
Section: Discussionmentioning
confidence: 99%
“…Some health facilities have already received international accreditation certificates, but the vast majority of the health facilities still require targeted efforts to improve the quality of care. [21][22][23][24][25] A sustainable country-wide system for infection control trainings should be institutionalized, and specific HIV-related exercises could be integrated into it, such as risk assessment exercises or case studies in PLWHA. This would help health care workers make the missing link between standard infection control measures and HIV as well as help mitigate the fear of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most HMCs were unable to hold regular meetings and we found it difficult to support them in a systematic way. It has been noted that the VDC secretary has many duties and low priority is often given to HMC issues [12], and regular HMC meetings and follow-up support are important for the success of locally managed interventions [12,29,30].…”
Section: Study Limitationsmentioning
confidence: 99%